Pendekatan Ma‘nā-Cum-Magzā Atas Kata Ahl (An-Nisā’/4: 58) dan Relevansinya Dalam Konteks Penafsir Di Indonesia Kontemporer - Iin Parninsih; Muhammad Alwi HS (Lajnah Pentashihan Mushaf Al-Qur'an, 2020)
This article analyzes the meaning of contextual word of ahl in surah an-Nisa'/4: 58 through the approach of ma‘na-cum-magza of Sahiron Syamsuddin’s which was then linked with the context of the Qur’anic scholarship in Indonesia. In the understanding of the revelation era, ahl refer to Usman ibn Talhah as a man who was expert in keeping the key of the Ka’bah. The meaning of the word ahl was apparently not a single one, but experiencing variations between one interpretation and others, from classic to modern-contemporary. So the meaning of ahl can be developed in the current context of Indonesia, including the context of the Qur’anic scholarship. This article discussed the initial understanding (ma‘na) ahl through context analysis (micro and macro) and linguistic analysis (intra-textuality and inter-textuality) critically. Furthermore, this study draws significant understanding of ahl which is linked with the discourse of Qur’anic scholarship in Indonesia as the person who studies the Qur’an seriously. The term ahl thus could legitimize the Qur’anic scholar as ahl Al-Qur’ān. Who has a comprehensive, responsible, to be fair in interpreting the Qur’an. They are those are the Qur’anic scholars who have a competence and responsibility and just attitude in interpreting the Qur’an. Keywords: Ma‘na-cum-magza, contextual interpretation, Sahiron Syamsuddin, ahl.